Influence of cleaning methods on bond strength to saliva contaminated zirconia. Issue 6 (30th October 2018) - Irmak, Özgür; Yaman, Batu Can; Orhan, Ekim Onur; Kılıçarslan, Mehmet Ali; Mante, Francis K.; Ozer, Fusun
Abstract: Objective: To evaluate the influence of saliva contamination and cleaning procedures on shear bond strength (SBS) of a self‐adhesive resin cement (SAC) to zirconia surfaces. Materials and Methods: A total of 160 sandblasted zirconia blocks were randomly divided into eight groups as follows: No saliva contamination, no cleansing (NC‐NC); contamination with saliva, no cleansing (SC‐NC); no saliva contamination, cleansing with a zirconia primer (ZP; Z‐Bond, Danville Materials, Inc., S. Ramon, California) (NC‐ZP); contamination with saliva, cleansing with ZP (SC‐ZP); no saliva contamination, cleansing with hydrofluoric acid (HF; Ultradent Porcelain Etch; Ultradent Products, South Jordan, Utah) followed by cleansing with ZP (NC‐HF‐ZP); contamination with saliva, cleansing with HF followed by cleansing with ZP (SC‐HF‐ZP); cleansing with ZP, contamination with saliva, cleansing with ZP (ZP‐SC‐ZP); application of ZP, contamination with saliva, cleansing with HF followed by cleansing with ZP (ZP‐SC‐HF‐ZP). Cylindrical resin composite blocks were luted to the zirconia surfaces with SAC (Clearfil SA Cement Automix, Kuraray, Inc., Tokyo, Japan). Specimens were subjected to shear forces at a cross‐head speed of 0.5 mm/min. Data were analyzed with Analysis of Variance and Tukey tests (α = 0.05). Results: The bond strength values to zirconia were significantly influenced by saliva contamination ( P < .05). The SC‐NC group showed the lowest bond strength values (5.6 ± 1.4 MPa; P < .05). All cleansing or pretreatment agents improved the bond strengths when compared to noncleansing groups, NC‐NC and SC‐NC. Conclusion: In situations where saliva contamination is deemed unavoidable, application of ZP after try‐in of the zirconia restoration could be beneficial for the accurate cementation. Clinical Significance: During try‐in sessions of fixed dental prostheses, zirconia ceramic restoration may come into contact with saliva and surfaces should be cleansed to obtain an optimal surface for adhesion. Application of zirconia primer to the sandblasted zirconia surface is recommended whether the surface is contaminated with saliva or not.